The association between sugar-sweetened beverage availability in school vending machines and school staff sugar-sweetened beverage consumption - Rauzon, Suzanne (Prev Med Rep, 2020)
Reducing sugar-sweetened beverage (SSB) consumption is a leading strategy to help combat high rates of adult obesity and overweight. Regulating SSB sales in schools has reduced access among youth. However, current federal school nutrition standards are focused on student rather than staff environments (i.e. school staff lounges). This study examines the association between the availability of SSBs in school vending machines and school staff SSB consumption. The study sample included 51 public schools in California, Oregon, Washington, Maryland, and Washington DC participating in an evaluation of Kaiser Permanente’s Thriving Schools initiative in school year 2017–18. Data collection included: 1) observations of school cafeterias, staff lounges, stores and outdoor snack areas for the presence of, and content in, vending machines, and 2) an online survey of school staff about their SSB consumption. Fifty-nine percent (n = 1586) of staff responded to the survey; 1229 (77% of respondents) reported on SSB consumption. Thirty percent of schools had staff lounges with SSB vending machines and 34% of staff reported drinking ≥1 SSBs/day. On average, the probability of consuming ≥1 SSBs/day was 6.6% greater in staff in schools with SSBs available in staff lounge vending machines (95% CI: 0.11%, 13.12%). Staff in schools with SSB vending machines in staff lounges were more likely to report consuming ≥1 SSBs per day compared to staff without SSB vending in staff lounges. Examining the impact of extending SSB regulations to the entire school environment on school staff SSB consumption is an important next step.